Training structure, periodisation and the science of winning with Jan Olbrecht, PhD | EP#198 - Eriksson, M. (2020)
Jan Olbrecht is a former elite swimmer, holds a PhD in sports physiology and biomechanics, and has advised athletes who have won over 600 Olympic, World Championship, European Championship and Commonwealth Championship medals. His main drive is to translate science to the level where coaches can benefit from it, and one of the main outcomes of this drive is his excellent and highly influential book 'The Science of Winning' on periodisation, training structure, and using physiology to deliver peak performances.